2017
DOI: 10.1007/s00410-017-1423-4
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of the crystal mush on the floor of the Bushveld magma chamber

Abstract: The thickness of the crystal mush on magma chamber floors can be constrained using the offset between the step-change in the median value of dihedral angles formed at the junctions between two grains of plagioclase and a grain of another phase (typically clinopyroxene, but also orthopyroxene and olivine) and the first appearance or disappearance of the liquidus phase associated with the step-change in median dihedral angle. We determined the mush thickness in the Rustenburg Layered Suite of the Bushveld Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 47 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…In these cumulate sequences, compaction is typically stopped when additional minerals crystallize (cpx or plagioclase) and block melt escape at ca. 20% interstitial melt (Holness et al., 2017). Considering that cooling from below does not occur in a magma ocean scenario, we consider trapped melt fractions ≤5% realistic (i.e., near the compaction threshold), yet use 2% and 20% as lower and upper bounds.…”
Section: What Stratification Can Be Expected At the End Of Lunar Magm...mentioning
confidence: 99%
“…In these cumulate sequences, compaction is typically stopped when additional minerals crystallize (cpx or plagioclase) and block melt escape at ca. 20% interstitial melt (Holness et al., 2017). Considering that cooling from below does not occur in a magma ocean scenario, we consider trapped melt fractions ≤5% realistic (i.e., near the compaction threshold), yet use 2% and 20% as lower and upper bounds.…”
Section: What Stratification Can Be Expected At the End Of Lunar Magm...mentioning
confidence: 99%
“…They used microstructural stepchanges in the latent heat accompanying the appearance of apatite to suggest that the mush thickness in the centre and eastern parts was only a few metres thick, increasing to c. 100 m in the western part of the intrusion (all at the UZa-UZb boundary). Similar studies of the Rustenburg layered suite of the Bushveld Complex (Holness et al 2017d) suggest a mush thickness of the order of a few metres and that neither gravitationally driven compaction nor compositional convection were likely to have been important processes during solidification. It was also suggested that adcumulates are most likely formed at the top of the mush during primary crystallisation.…”
Section: Effects Of Granophyre Migration On Calculated Trapped Melt C...mentioning
confidence: 82%
“…In conclusion and paraphrasing Holness et al (2017d) and Holness (2018), the main issue with some of these arguments is that they are often based on bulk geochemistry and an arbitrary model of fractionation involving primocrysts and an interstitial trapped liquid. This interstitial liquid is now thought likely to have undergone significant in situ fractionation, including the preferential loss of at least one immiscible component.…”
Section: Effects Of Granophyre Migration On Calculated Trapped Melt C...mentioning
confidence: 99%
“…The total absence of interstitial quartz from the mottle (Online Appendix 5) and the paucity of quartz in the anorthositic host rock (Online Appendix 7) is unusual compared to some other UCZ rocks (e.g., Holness et al 2017) and anorthosites in the Stillwater complex (Salpas et al 1983) where quartz may constitute up to a few percent of the rock and is thought to have crystallised from trapped liquid. The absence of quartz in the mottle thus suggests that primary quartz was removed during crystallisation.…”
Section: Paucity Of Quartzmentioning
confidence: 99%